ANTARA ADAT DAN HUKUM NEGARA TINJAUAN KEBIASAAN HUKUM MASYARAKAT NGAWEN TERHADAP PERCERAIAN NON-YUDISIAL - Payana, Fahmi Dwi; Wibowo, Muh. Kurniawan Budi; Sulistyowati, S (AL HUKMU: Journal of Islamic Law and Economics, 2025)
Problems of married couples often arise in the middle of a household ark, because of the big problems some couples choose to divorce as a way out. However, there are husbands or wives who carry out divorce but do not want to take care of the administration of their divorce, in other words, they are satisfied with religious divorce not under Indonesian Positive law. Therefore, this study aimed to understand the problems of couples who divorce but do not go through religious courts, so as to get the right solution for the people of Ngawen Subdistrict. This research uses a qualitative-descriptive research method with an ethnographic approach, with data collection techniques through documentation, direct interviews with sub-district employees, villages and residents who divorce without going through religious courts in order to get complete information and data, and observation. Data analysis uses content analysis techniques. To test the validity of the data, credibility, transferability, dependability, and confirmability were used. The results of the study show that the community in Ngawen Subdistrict consciously strives for its citizens to be sakinah, mawaddah, wa rahmah, even if they are unable to achieve this situation, the community wants divorce to be legalized in the Religious Court so that the rights of divorced couples are guaranteed